Modern Islamic authority and social change. - Bano, Masooda (Edinburgh University Press, 2018)
This volume focuses on the four most influential Islamic authority structures with a visible following among Muslims around the globe: Al-Azhar (Egypt); Saudi Salafism (Saudi Arabia); Deoband (South Asia); Diyanet (Turkey).